SOSIO-KULTURAL TAFSIR AL-QUR’AN MELAYU NUSANTARA : KAJIAN ATAS TAFSIR AL-AZHAR KARYA HAMKA - Halimatussa'diyah Halimatussa'diyah; Apriyanti Apriyanti (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2018)
This article aims to show the importance of the socio-cultural approach in interpreting the Qur'an. Here, an exegete seeks to produce interpretive products through a thorough understanding of the texts of the Qur'an, then explains the intended meanings and seeks to relate the texts of the Qur'an with social reality and culture context in society. Hamka's Tafsir al-Azhar was chosen because the interpretation of al-Azhar was a popular interpretation in the third period in the development of interpretations in Indonesia. Al-Azhar's interpretation which is patterned with al-adabiy al-ijtima'iy approach, explains the social problems of society. The problems studied are women's leadership issues, inheritance and hijab. Hamka's interpretation of women's leadership is that men become leaders of women because men have the obligation to pay dowry to women. and also to treat his wife well. All of this shows that men are indeed leaders of women. The leadership comes from men instinct, while women have an instinct to be led. However, it is possible for women to become leaders if women have advantages over men. Men get twice the share of women in the distribution of inheritance because men's responsibility is heavier than women in property. Hamka does not view this inheritance difference from the physical aspects of women, but rather looks at the responsibilities given to men. The obligation of women to cover their genitals is to protect the honor of women and avoid mistreatment from other parties. Efforts to form a community of believers and morality are not only aimed at women, but also assigned to men.